Co-developmental trajectories of psychological need satisfactions at school: Relations to mental health and academic functioning in Chinese elementary school students. (August 2021) - Zhou, Jianhua; Huebner, E. Scott; Tian, Lili
Abstract: This study explored the co-developmental trajectories of autonomy, competence and relatedness need satisfactions at school and their relations to mental health and academic functioning in Chinese elementary school students. An accelerated longitudinal design was used with a sample of three cohorts (grade 3, grade 4, and grade 5) ( N  = 1070, 45.8% female; M age  = 9.44, SD  = 0.97) on four occasions at 6-month intervals. Parallel process latent class growth models revealed five heterogeneous patterns (i.e., Congruent-moderate; Congruent-high; Congruent-low; Congruent-decreasing; Low-autonomy, High-competence and relatedness), all of which significantly associated with time-varying mental health and academic functioning indicators. The findings highlight the importance of subgroup differences and possible cultural considerations in understanding the progression of psychological need satisfactions and the need for universal screening and dynamic monitoring of students' psychological need satisfactions at school and implementing more sophisticated interventions tailored to the unique characteristics of the relevant subgroups to promote optimal mental health and learning. Highlights: Children's need satisfactions at school fluctuated in a heterogeneous fashion. The findings revealed five co-developmental patterns of three need satisfactions. Students in the congruent-high group showed the best adjustment functioning. Autonomy need satisfaction in Chinese elementary students warrants more attention.